Innovative division of information systems of building enterprises according to the methods of economy and process technology/Konzeption zur neugliederung der baubetrieblichen informationssysteme nach betriebswirtschaftlichen und verfahrenstechnischen met - Reader, Siegfried (Journal of Civil Engineering and Management, 1997)
At the present time the implementation of building projects is impossible without using information technology. This process can be divided into 4 stages: 1) planning and constructing, 2) getting permissions, 3) building preparations, and 4) building peformance. Roughly speaking, decomposition of building activities includes two main spheres: technical and economic. Building enterprise information systems are open dynamic systems. They consist of active elements connected by material supply quantities. They also include elements showing their relations to the environment and to the client. When arranging this system, one must have in mind that the implementation of a building order should follow contract agreements with the aim of getting profit. Therefore all the deviations from guiding quantities should be avoided by compensating them. A developed building enterprise information system implies this regulating property. In this case, it is referred as cybernetic system. Contrary to the building site information systems oriented to the present time, the novelty of the new decomposition consists in that it does not deal with a pure control system and a model possessing partial systems, but with a building enterprise information system developed following modern methods of building enterprise as well as economic sciences and intended for achieving completeness and transparency. It ensures a reliable information pertaining to an important building process and permits to make timely decisions.Statybos įmonių informacinių sistemų naujoviškas skirstymas pagal įmonės ekonominį ir procesų technologijos metodusSantrauka. Šiandien statybos projektų įgyvendinti nepanaudojus informacinės technikos yra neįmanoma. Šį procesą galime skirstyti į keturis etapus: planavimą ir konstravimą, leidimų fazę, statybos paruošimą. ir statybos vykdymą. Statybinės veiklos suskaidymas grubiai apima dvi pagrindines sritistechninę ir ekonominę. Statybos įmonės informacinės sistemos yra atviros dinaminės sistemos. Jose egzistuoja aktyvūs elementai, kurie yra susieti materialiais tiekimo dydžiais. Taip pat jos turi elementus, kurie nurodo santykį su aplinka, o taip pat ir su užsakovu. Sudarant šią sistemą. reikia remtis tuo, kad statybos užsakymo įvykdymas vyktų pagal sutartinius derinimus su tikslu gauti pelną. Visi nukrypimai nuo vadovavimo dydžių turi būti kompensuojant pašalinti. Išvystyta statybos įmonės informacinė sistema turi šią. reguliuojančią. savybę. Tuomet ji apibūdinama kaip kibernetinė sistema. Priešingai, į dabartį orientuotų statybos aikštelių informatimių sistemų naujas suskaidymas yra toks, kad čia nekalbama nei apie gryną kontrolės sistemą, nei apie modelį su dalinėmis sistemomis, bet apie statybos įmonės informacinę sistemą, sukurtą pagal modernius statybos įmonės ir ekonomikos mokslų metodus, nukreiptus sukurti pilnumą ir transparenciją. Tai garantuoja patikimą informaciją apie svarbų statybos procesą ir leidžia priimti skubius sprendimus.Article in German.First Published Online: 26 Jul 2012